جريمتي البغي والسرقة والأحكام الخاصة بهما بين الشريعة الإسلامية والقانون الليبي - Hasanulddin, Mohd; Abdel Karem Abdel Rahem, Abdel Karem (2019)
People's relations with each other exist since ancient times and these relations developed when the number of people increased. Therefore, these relations needed principles and laws to control and maintain them properly, so it was necessary to have law in societies. Accordingly, there is a need for academic studies on political crimes because the subject is yet exhaustively studied, especially in the attempts to examine the legal provisions of political crimes such as the crimes of mutiny and theft and then compare these provisions of the positive laws illustrating the differences appear between these provisions in the light of the Islamic law, thus the research problem emergences at this point. The purpose of this research is therefore to explain the provisions of the political crimes (mutiny and theft) from the perspective of the Islamic law and the Libyan law. This research seeks to determine the Islamic Shariah laws pertaining to the crimes of mutiny and theft and compare them with the legal aspect and its various constitutions. This in turn positively impacts on the raising of the public awareness of the importance of comparative study. Furthermore, the importance of this study is also realized in the identifications of defects in the articles of the Libyan Political Crimes Law regarding the provisions of the crimes of mutiny and theft. The research findings concluded that the Islamic Shariah law divides political crimes into crimes of opinion and actual crimes. It furthers that actual crimes include any attack against the ruler individually or collectively target the regime as in mutiny. And that mutiny is one of the forms of political crimes classified under the Islamic law which Islam has devoted special system to deal with, classifying it as a serious major political crime.